2021
DOI: 10.3390/ijms22094374
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Sodium-Glucose Cotransporter-2 Inhibitors: Renoprotective Mechanisms beyond Glycemic Control

Abstract: Diabetes mellitus is a major cause of chronic kidney disease and end-stage renal disease. However, the management of chronic kidney disease, particularly diabetes, requires vast improvements. Recently, sodium-glucose cotransporter-2 (SGLT2) inhibitors, originally developed for the treatment of diabetes, have been shown to protect against kidney injury via glycemic control, as well as various other mechanisms, including blood pressure and hemodynamic regulation, protection from lipotoxicity, and uric acid contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Currently, there are three oral SGLT2 options approved by the U.S. Food and Drug Administration and European Medicines Agency, recommended for patients with type 2 diabetes mellitus and CKD with eGFR > 30 mL/min/1.72 m 2 . Studies indicated significant improvement in upregulation of angiotensin, reductions of UA, oxidative stress, arterial stiffness, inflammation, and body weight [ 93 ]. Other potential advantages from SGLT2 inhibitors may be reduction of anti-inflammatory, anti-oxidant, and anti-fibrotic markers [ 94 ].…”
Section: Available Treatment Option For Lowering Uric Acidmentioning
confidence: 99%
“…Currently, there are three oral SGLT2 options approved by the U.S. Food and Drug Administration and European Medicines Agency, recommended for patients with type 2 diabetes mellitus and CKD with eGFR > 30 mL/min/1.72 m 2 . Studies indicated significant improvement in upregulation of angiotensin, reductions of UA, oxidative stress, arterial stiffness, inflammation, and body weight [ 93 ]. Other potential advantages from SGLT2 inhibitors may be reduction of anti-inflammatory, anti-oxidant, and anti-fibrotic markers [ 94 ].…”
Section: Available Treatment Option For Lowering Uric Acidmentioning
confidence: 99%
“…Chino et al revealed that the urinary excretion rate of uric acid strongly correlated with the urinary glucose excretion, demonstrating the relation between SUA and glycosuria [ 86 ]. Raised glucose concentration resulting from SGLT2i administration could also disturb the reabsorption of uric acid in the proximal tubule through GLUT9b [ 87 ]. After removing the studies that were conducted on CKD patients, the SUA reduction was increased, which is consistent with the proposed model for uricosuric effects of SGLT2i by Chino et al [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms are considered to be the mechanism by which SGLT2 inhibitors prevent and improve heart failure ( Figure 2 ) [ 73 , 74 , 75 , 76 ].…”
Section: What Is An Effective Treatment?mentioning
confidence: 99%